Espelho, espelho meu: estilizando o envelhecimento em Cronos e Kairòs - Arruda, Thaise Chaves de (2013)
This paper addresses the way how the subject is treated aesthetics of aging and aesthetics of existence in academia. The strategy used was to Bibliographic Search through the collection of data of the journal Academic Kairos - PUC / SP, published from 1998 to 2012. Given the importance that the issues related to body image and to care for themselves are getting in the media and the biopsychosocial context, it has become essential that the academy contributed to the themes: aesthetics of aging - related to the aging body, and aesthetics of existence - referring to the stylized and creative ways to grow old, posing a major challenge for the humanities. Research on body aesthetics, until very recently, were neglected, however, have raised considerable interest on the part of the Humanities and related fields, based on the growing Western cultural manifestations that overvalue keep the body young. Given this concern, there are also issues related to the well-being, considering the subjectivity of the subject, with respect to "self care" in envelhecimento.Os articles analyzed in this dissertation were written by authors from different areas of knowledge, demonstrating how the above theme begins to move the locus of academic production and its importance within the Gerontology